Screening of cancer cervix: Pap smear in rural India - A., Parimala; Sharma, Nidhi; Srinivasan, Jayashree K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The incidence of cervical premalignant lesions in rural India is likely to be high due to presence of several risk factors like early marriage, early coitarche and multiparity. Hence prospective cross sectional study was conducted to find the incidence of pre-invasive state and cancer of cervix in women between the age group 30 and 60 years, visiting Thirumazhisai health centre by Pap’s smear method. Methods: Cervical mucosa is scraped, using Ayre spatula a 360° turn is made at the transition zone and smeared on a slide and papanicolaou stain is applied and the slide is examined under microscope. If Pap’s smear confirms low/high grade lesion, biospy is done to confirm the finding. The result is analysed for pre-invasive state. Results: Out of the cases (107) examined with in the study period, 36.45% were normal. Out of the rest 47.05% had an inflammatory smear, 14.7% had active bacterial infection, 17.65% had active candida infection and 5.88% had high-grade intraepithelial lesion (CIN 3). Conclusions: The incidence of high-grade lesion for cervical cancer is high among the rural population and they are susceptible to develop the cancer. Regular screening for cancer of uterine cervix is of need among people of lower socio economic status. Awareness should be created on cervical cancer and its complications.